2008
DOI: 10.1016/j.ymgme.2008.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Molecular consequences of the pathogenic mutation in feline GM1 gangliosidosis

Abstract: G M1 gangliosidosis is an inherited, fatal neurodegenerative disease caused by deficiency of lysosomal β-D-galactosidase (EC 3.2.1.23) and consequent storage of undegraded G M1 ganglioside. To characterize the genetic mutation responsible for feline G M1 gangliosidosis, the normal sequence of feline β-galactosidase cDNA first was defined. The feline β-galactosidase open reading frame is 2010 base pairs, producing a protein of 669 amino acids. The putative signal sequence consists of amino acids 1-24 of the β-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
36
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 56 publications
(72 reference statements)
10
36
1
Order By: Relevance
“…Indirect immunofluorescence and confocal microscopy imaging were performed as previously described [37]. Primary/secondary antibodies and nuclear staining were as previously reported [36].…”
Section: Indirect Immunofluorescence Staining and Confocal Microscopymentioning
confidence: 99%
“…Indirect immunofluorescence and confocal microscopy imaging were performed as previously described [37]. Primary/secondary antibodies and nuclear staining were as previously reported [36].…”
Section: Indirect Immunofluorescence Staining and Confocal Microscopymentioning
confidence: 99%
“…mutations, used in this study are indicated in Table 1 along with their response to NN-DGJ. Immortalized fibroblasts cell lines from normal (SV3) and GM1 cats (GM1 SV3) were generated in the D. Martin laboratory [28] by calcium phosphate transfection of primary fibroblasts with the plasmid pSV3-DHFR (American Type Culture Collection) containing the large T antigen of Simian Virus 40.…”
Section: Cell Lines Tissue Culture and Small Molecule Treatmentmentioning
confidence: 99%
“…Indirect immunofluorescence and confocal microscopy imaging for human or feline fibroblasts in the presence or absence of NN-DGJ were performed as previously reported [28].…”
Section: Indirect Immunofluorescence Staining and Confocal Microscopymentioning
confidence: 99%
See 2 more Smart Citations